Protective Effect of Combination Commercial Black Seed Oil (Nigella sativa) and Honey Against Cisplatin-Induced Hepatotoxicity in Rats - Siddiq, Andri Muhrim; Ilmiawan, Muhammad In'am; Handini, Mitra (Muhammadiyah Medical Journal, 2020)
Background: The chemotherapeutic use of cisplatin (CP) is restricted because of its hepatotoxicity induced by oxidative stress. Malondialdehyde (MDA) is a secondary product of lipid peroxidation as a biomarker of oxidative stress. Individual administration of black seed oil (BSO) or honey (H) demonstrated hepatoprotective effect in rats. Interaction of both substances when administrated as combination can be evaluated using combination index (CI) to quantitatively depict synergism (CI1), additive (CI=1) and antagonism effect (CI1). Objective: to know the combination effect of BSO and honey on rat liver tissue given CP exposure. Methods: This study used 30 rats were divided into 10 groups. Normal group (N); Negative control group (NC); P1-P4 groups were administerated BSO (1 and 2 mL/kg) and honey (3.7 and 7.4 mL/kg); P5-P8 groups were combination of BSO and H. P1-P8 groups were given BSO and honey orally for 21 days. On the 18th day, NC and P1-P8 groups were given CP 8 mg/kg intraperitoneally, while the N group was given NaCl 0.9% 1 mL/kg intraperitoneally. Result: Malondialdehyde (MDA) levels were found to be lower in P1-P8 groups compared to negative control group and P6 and P7 groups have levels equivalent to MDA levels of normal control group (p 0.05). Conclusion: Combination of BSO and honey provides a protective effect on cisplatin-induced rat liver tissue damage indicated by reduced MDA levels, but all combination group showed antagonism effect.